2014
DOI: 10.1021/cs500611g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reaction of Acetaldehyde on Shape-Controlled CeO2 Nanocrystals: Elucidation of Structure–Function Relationships

Abstract: CeO 2 cubes with {100} facets, octahedra with {111} facets, and wires with highly defective structures were utilized to probe the structure-dependent reactivity of acetaldehyde. Using temperature-programmed desorption (TPD), temperature-programmed surface reactions (TPSR), and in situ infrared spectroscopy, it was determined that acetaldehyde desorbs unreacted or undergoes reduction, coupling, or C−C bond scission reactions, depending on the surface structure of CeO 2 . Room-temperature FTIR indicates that ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
151
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 53 publications
7
151
0
Order By: Relevance
“…Furthermore, addition of dopants into the ceria have been demonstrated to modify the Pt-support interaction and consequently the resulting WGSR activity, having a direct effect on the reaction mechanism [15,16]. We have recently demonstrated that the oxygen storage capacity and low temperature reducibility of the ceria can be tuned by varying its morphology at the nano-scale by selectively exposing different crystal planes [17], leading to further studies by other groups [18,19]. In this paper, we demonstrate the relationship between the surface chemical and physical properties of nanostructured ceria and the resulting platinum-support interaction, reducibility of ceria and consequently, WGSR activity, providing relevant insights for future catalyst design in this field.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, addition of dopants into the ceria have been demonstrated to modify the Pt-support interaction and consequently the resulting WGSR activity, having a direct effect on the reaction mechanism [15,16]. We have recently demonstrated that the oxygen storage capacity and low temperature reducibility of the ceria can be tuned by varying its morphology at the nano-scale by selectively exposing different crystal planes [17], leading to further studies by other groups [18,19]. In this paper, we demonstrate the relationship between the surface chemical and physical properties of nanostructured ceria and the resulting platinum-support interaction, reducibility of ceria and consequently, WGSR activity, providing relevant insights for future catalyst design in this field.…”
Section: Introductionmentioning
confidence: 91%
“…[8][9][10][11] This manifests itself through different selectivity or improved activity, which enables the catalyst to be operated at lower temperatures. Numerous theoretical [12][13][14] and experimental [8][9][10][11][15][16][17][18][19][20][21] investigations have revealed that nanoshaped CeO 2 (nanocubes and nanorods) with well-defined {100} and {110} reactive planes show higher catalytic activity than conventional and thermodynamically more stable polyhedral CeO 2 nanoparticles. This is likely connected to lower activation energy for oxygen vacancy formation over {110} and {100} planes, compared to {111}.…”
Section: Introductionmentioning
confidence: 99%
“…CO oxidation [23][24][25], NO reduction [26] and WGS reaction [27]. Ceria nanorods exhibited superior activity in oxidation of CO, 1,2-dichloroethane, ethyl-acetate and ethanol [19,[28][29][30], methanol conversion in presence of CO 2 [31], methanol [32] and acetaldehyde decomposition [33] compared to ceria cubes and octahedra. Moreover, shuttleshaped particles composed of closely packed ceria nanorods displayed higher activity for CO oxidation compared to ceria nanorods [34], which has been attributed to enhanced porosity, surface area and oxygen deficiency of these nanoshapes compared to ceria rods.…”
Section: Introductionmentioning
confidence: 99%